Psychological distress and decision‐making factors for prophylactic bilateral mastectomy in cancer‐unaffected BRCA1/2 pathogenic variant carriers. Issue 4 (7th March 2023) - Isselhard, Anna; Tüchler, Anja; Dick, Julia; Scherer, Anne; Aue, Viktoria; Schmutzler, Rita K.; Rhiem, Kerstin
Abstract: Objective: Women carrying a BRCA1/2 pathogenic variant have an increased risk for breast cancer and may opt for risk‐reducing bilateral mastectomy. In this study, we examine which demographic, psychosocial, and personality factors are associated with their decision to undergo risk‐reducing bilateral mastectomy. Methods: Cancer‐unaffected women with a pathogenic variant in BRCA1 or BRCA2 were recruited before receiving their genetic test result and completed follow‐up including decision to undergo mastectomy over 6–8 months after genetic test result disclosure. Anxiety, depression, breast cancer worry, personality and sociodemographic data were assessed. Results: A total of 125 cancer‐unaffected women were included in the analysis. Participants were found to have higher anxiety levels than the general female population regardless of mastectomy decision. Breast cancer worry was higher among women who opted for risk‐reducing mastectomy and did not decrease over time. By contrast, women who did not opt for surgery experienced decreasing levels of breast cancer worry. Regression analysis found that women with a pathogenic variant in BRCA1, younger women and women with higher breast cancer worry were more likely to opt for surgery. Conclusions: Our study provides valuable insights into the factors that influence women with a BRCA1/2 pathogenic variant to undergo risk‐reducing mastectomy. These findings may be helpful in understanding individual differences in decision‐making concerning preventive options and show the need to address negative anticipatory feelings associated with carrying a pathogenic variant in a high breast cancer risk gene in clinical care.